THE PORTRAYAL OF REJECTIVE BEHAVIORS TOWARD AFRICAN-AMERICAN PEOPLE IN LANGSTON HUGHES’ NOT WITHOUT LAUGHTER NOVEL - Fajriati, Dwi Nor; Asanti, Chris; Muhajir, Fatimah (Fakultas Ilmu Budaya Universitas Mulawarman, 2022)
This research analyzed Langston Hughes’ novel Not Without Laughter. The novel was published in1930. The novel talks about the condition of the black American family in the early twentieth century. This research discussed the issue of rejective behaviors occurring towards white people towards African-American family life. Meanwhile, the researcher focused on analyzing two research questions. First, the researcher analyzes the kinds of rejective behavior portrayed in Not Without Laughter novel. Second, the researcher analyzed how the responses of black people characters towards the rejective behavior portrayed in Not Without Laughter novel. Under the paradigm of qualitative research, this research employed a mimetic approach. The data were obtained from words, sentences, clauses, phrases, and paragraphs that are related to the act of rejective behaviors experienced by African-American people and their reaction toward these rejective behaviors that are suitable with Allport’s theory. The results of this research showed that there are three types of rejective behavior they are verbal rejection, discrimination, and physical attack. The results also showed that the response of rejective behavior toward African-American family life in the novel are obsessive concern response, withdrawal and passivity response, clowning response, self-hate response, sympathy response, and fighting back response. From the results it can be implied that both male and female characters responded differently to the rejective behaviour that happened to them.